Cocoa Farmer's Use Of Approved Pesticides And Compliance With Safety Standards In Obuasi Municipality, Ghana - Hyde-Cooper, Wilhemina; Tham-Agyekum, Enoch Kwame; Bakang, John-Eudes Andivi; Ntem, Supernatural; Ankuyi, Fred; Mohammed, Rubaba (International Journal on Food, Agriculture and Natural Resources, 2024)
Amidst the agricultural landscape of Ghana lies a complex interplay of practices governing the use of approved pesticides and adherence to safety standards among farmers. By analysing data gleaned from 400 farmers through the multistage sampling technique, our aim is reveal the multifaceted influences that shape farmers' decisions in the use of approved pesticides and safety compliance. Age, education, marital status, farm ownership, experience, farm size, access to equipment and services, cooperative membership, secondary occupations, and income, significantly influence farmers' choices in the use of approved pesticides. Furthermore, compliance with safety protocols is found to be influenced by factors such as farm size, access to extension services, and the perceived relative advantage of pesticides. We advocate for policies that promote the use of approved pesticides and prioritise safety standards in agricultural practices. This may include strengthening regulatory frameworks, incentivising sustainable farming practices, and enforcing penalties for non-compliance with safety regulations.